DEVELOPMENT OF A BIO-MEMS CANTILEVER-BASED BIOSENSOR FOR THE RAPID, LABEL-FREE DETECTION OF THE AVIAN INFLUENZA VIRUS - Rocha, Thiago; Mendes, Clara; Lima, Rafaela (Yayasan Adra Karima Hubbi, 2025)
Avian influenza virus remains a significant threat to global public health, poultry industries, and food security due to its high transmissibility and zoonotic potential. Rapid and reliable detection is essential for early outbreak control, yet conventional diagnostic methods are often time-consuming, laboratory-dependent, and rely on labeled reagents, limiting their applicability in field and point-of-care settings. This study aims to develop a Bio-MEMS cantilever-based biosensor capable of rapid, label-free detection of the avian influenza virus with high sensitivity and specificity. An experimental Bio-MEMS approach was employed, involving microfabrication of silicon cantilevers, surface biofunctionalization with virus-specific recognition elements, and real-time mechanical sensing of virus–receptor interactions. The biosensor’s performance was evaluated by measuring cantilever deflection responses under controlled exposure to varying viral concentrations. The results demonstrate stable baseline behavior, low noise levels, and clear concentration-dependent deflection signals, achieving rapid detection within minutes and a low limit of detection without signal amplification. Non-target analytes produced negligible responses, confirming high specificity. In conclusion, the developed Bio-MEMS cantilever-based biosensor provides an effective platform for rapid, label-free detection of avian influenza virus. This technology shows strong potential for integration into portable diagnostic systems and could be adapted for surveillance of other viral pathogens.